Immigrant integration and youth mental health in four European countries - Mood, C; Jonsson, J; Låftman, S (Oxford University Press, 2016)
The mental health of children of immigrant background compared to their majority peers is an important indicator of integration. We analyse internalizing and externalizing problems in 14–15-year-olds from England, Germany, the Netherlands, and Sweden (n=18,716), using new comparative data (Children of Immigrants Longitudinal Survey in Four European Countries). Studying more than 30 different origin countries, we find that despite potential problems with acculturation and social stress, children of immigrants—particularly from geographically and culturally distant countries—report systematically fewer internalizing and externalizing problems than the majority population, thus supporting the ‘immigrant health paradox’ found in some studies. However, surprisingly, we do not find that this minority advantage changes with time in the destination country. Externalizing problems are most prevalent in our English sample, and overall Swedish adolescents show the least mental health problems. A plausible account of our results is that there is a positive selection of immigrants on some persistent and intergenerationally transferable characteristic that invokes resilience in children.